The effect of transportation on the stability of hematological examination - Gilang Nugraha; Notrisia Rachmayanti; Moch. Sahri; Maulana Bagas Syaifulloh; Salsabillah Karunia Sugiarto (Jurnal Teknologi Laboratorium)
Transportation accounts for quite large errors up to 12% of the total errors. The error factor in this transportation activity comes from sending specimens that are too long and storage temperatures that are not right. Hematological examination is an examination that is often performed in various health services. The purpose of this study was to determine the stability of the hematological examination of blood samples transported for 1 hour and 2 hours at room temperature and cold temperatures. This study is a laboratory experimental study. Observations before treatment were controls, and treatments were carried out after 1 hour and 2 hours of transportation at room temperature and cold temperatures. This research was conducted at an average ambient temperature of 33.4ºC and humidity of 45%, room temperature of 27.8ºC and humidity of 43%, cold temperature of 4.5ºC and humidity of 52%, and average shock of 54.9. The results showed that the parameters of Hgb, PLT, WBC, and NEUT were stable for up to 2 hours in both room temperature and cold conditions. Meanwhile, the stability of LYMPH parameters is only capable at room temperature for 2 hours. Parameters Hct, RBC, MCV, MCHC, and MXD there are differences in the results of the examination at cold temperatures after 1 hour and 2 hours. However, the parameters of RBC, MCV, and MXD were stable for up to 1 hour at room temperature. We conclude that the hematological examination is stable for up to 1 hour with the recommended storage at room temperature. Only Hgb, PLT, WBC, and NEUT tests are stable for up to 2 hours in both room temperature and cold conditions.